Complete house furnishers: the retailer as interior designer in nineteenth-century London - Clive Edwards (2013)
This research paper considers the history of a particular moment in the development of the interior decoration/design business. Although the history of interior design practice has been well charted as ‘‘art/design history,’’ the business and professional history has been somewhat neglected, except for work on particular firms. The issues examined relate to four particular aspects. The first covers the distinctions between decorators, upholsterers, furnishers, and architects and how these differences were reflected in the work undertaken. Related to this is a brief examination of why many architects ignored interior work. Secondly, is the nature of the customer base and how it reacted in response to changing social and economic factors. Thirdly, there are the issues of marketing and promotion that were aimed at a much wider audience than architects would expect, and finally a consideration of the house furnisher as a foundation for the development of the professional interior decorator/designer. To address these issues, the paper offers an overview of the rise, maturity, and change of the house furnisher as the most important contributor to the supply of interior design/decoration advice and products in the second half of the nineteenth century. By taking case studies of important players in the field, the paper will consider why architects gave up their role as arbiters of taste in interior works, and how the house furnishing businesses took over. This is of some interest as it not only explores an issue that still remains in the interior design world—the notion of who controls the work, but also explores the nature and pre-history of professional interior design service providers in the period. Although the scope of this essay is potentially wide ranging, it is limited to the second half of the nineteenth century and focuses on London for its case studies. Through a consideration of primary sources, often using the trade press for commentaries, a sense of the contemporary issues is made. In addition, the recent work by scholars in the field is used to interpret the changes described. As a foundation for the subsequent development of a profession, the house furnisher had laid a number of ground rules. Apart from the issue of the control of work, they encouraged the development of specialized knowledge, and they recognized the importance of training and education, and to some extent, exercised control of access to the industry.